Sifat Fisikokimia Tepung Gembili (Dioscorea esculenta (Lour.) Burk.) Hasil Fermentasi dengan Penambahan Inokulum Bakteri Selulolitik dan Bakteri Asam Laktat - Saskiawan, Iwan; Nafi’ah, Maidatun (JURNAL BIOLOGI INDONESIA, 2014)
Gembili is a tuber plant which is usually used as an alternative food source. It containts high carbohydrates andpotentially to be developed into flour. Fermentation of gembili is the method to improve the quality of gembiliflour. The objective of this research was to study the physicochemical properties of fermented gembili flour with theaddition of cellulolytic (BS) and lactic acid bacteria (BAL). There were four treatments, namely naturalfermentation without the addition of neither BS nor BAL, with the addition of BS, with the addition of BAL, andwith the addition of BS and BAL. Fermentation was carried out for three days. Temperature, pH, the number ofbacteria, as well as cellulase and amylase activity were observed every day. The studies of physical properties ofgembili flour were the color, flavor, texture, and yield. Furthermore, the chemical properties included water, ash,carbohydrate, fat, and protein content. Data were analyzed by ANOVA and continued by LSD test at 5%significance level. It showed that the physical properties of flour color in the treatment of BS fermentation werebetter than other treatments. However, the aroma and texture did not show any significant difference. Thechemical properties showed no significant difference among all treatments.Keywords: fermented gembili flour, physicochemical